Enhancing Islamic Religious Education at SMPN 03 Palopo: Validity and Practicality of E-Modules Utilizing Canva and Heyzine Applications - Ismail, Hajar; Hasriadi, Hasriadi; Thaha, Hisban (South Sulawesi Education Development (SSED), 2023)
This research is entitled Development of E-modules Based on Canva and Heyzine Applications in Islamic Religious Education Subjects at Junior High School (SMP) Negeri 03 Palopo. This study aimed to determine the validity and practicality of e-modules based on Canva and Heyzine applications in Islamic Religious Education subjects at SMPN 03 Palopo. This research uses the R&D (Research and Development) research type with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of this study indicate that the Islamic Religious Education e-module from the validity test has met the criteria of very valid with a score of 84.21% by media experts, 95% by material experts and 81.81% by linguists. It meets the practical criteria with a score of 98% by educators and 91% by students.